Serum Pepsinogen and Gastrin Levels: Reliable Markers to Predict Small Intestinal Bacterial Overgrowth - Kim, Dae Bum; Jo, Ik Hyun; Paik, Chang-Nyol; Kim, Yeon-Ji; Lee, Ji Min (Turkish Journal of Gastroenterology, 2022)
Background: Serum pepsinogen, a useful indicator of gastric acidity, could reflect small intestinal bacterial overgrowth. The aim of thisstudy is to evaluate the relationship between small intestinal bacterial overgrowth and profiles including pepsinogen or gastrin.Methods: We conducted a prospective study with 62 patients with a functional gastrointestinal disorder. All patients underwentglucose breath test for small intestinal bacterial overgrowth, immediately followed by upper endoscopy to survey gastric injury andCampylobacter-like organism test for Helicobacter pylori and serum laboratory tests including gastrin, pepsinogen I and II.Results: The positivity to small intestinal bacterial overgrowth was 17.7%. Significantly, low total hydrogen concentration during aglucose breath test, low prevalence for gastric injury, and high H. pylori positivity rate were shown in groups with pepsinogen I/II ratio≤ 3.5 compared to those with pepsinogen I/II ratio > 3.5 or in groups with serum gastrin > 35.4 pg/mL comparing to those with serum≤ 35.4 pg/mL, respectively. A high gastrin level was independently associated with H. pylori infection. A proportionally correlated tendency between pepsinogen I/II ratio and total hydrogen concentration was shown, whereas that of inverse proportion between H2 andgastrin was observed. Old age was solely independent predicting factor for small intestinal bacterial overgrowth (P = .03) in the multivariate analysis.Conclusion: Old age was significantly related to the presence of small intestinal bacterial overgrowth in functional gastrointestinaldisorder patients. Although pepsinogen and small intestinal bacterial overgrowth seem irrelevant, elevated gastrin level may cautiouslyindicate a decreased breath hydrogen concentration. Further studies should consider the function of intestinal motility and gastric acidity in patients with hydrogen-producing small intestinal bacterial overgrowth.